Effectiveness of group counseling in smoking cessation program amongst adolescent smokers in Malaysia (Medical Journal of Indonesia, 2010)
Aim: To assess the effectiveness of groups counseling for smoking cessation among secondary school students. Methods: This study was conducted among secondary school students in two districts in Selangor Malaysia, during July 2005 until August 2006. Upon screening, 346 students were randomly assigned into intervention group (IG) (n=158) and non intervention group (NIG) (n=188). IG underwent structured group counseling regularly for four months, while no group counseling was given to the NIG but subjected to the regular smoking cessation activities organized by their respective schools. Knowledge and attitude towards smoking and quit rate were measured in both groups before intervention, and at 4, 8, and 12 months after intervention. Results: Revealed that students in IG had significantly higher knowledge scores than those in NIG during follow-up visits (24.29+7.97 vs 23.58+8.44 on the first visit), (29.10+8.52 vs 24.09+8.69 on the second visit) (26.59+8.26 vs 22.08+8.04 on the third visit), and (25.54+8.34 vs 21.26+9.60 on the fourth visit). Attitude scores were not significantly different in both groups. Quit rate at four months after intervention was signifi cantly higher in IG as compared to the NIG (45%; 71/158 vs 32%; 60/188) (P=0.013). Conclusion: Group counseling is very effective in improving the respondents' knowledge and quite rate, but not their attitudes toward smoking. (Med J Indones 2010; 19:273-9)